Entrance of the Garbhagriha of the Hanuman Garhi temple complex - Temples of India Project Team (Jio Institute, 2024)
The entrance of the garbhagriha (sanctum sanctorum) of the Hanuman Garhi temple complex and the enshrined Hanuman figure. This temple complex gets its name from the life-size figure of Hanuman in the temple. The doorframe of the temple is repurposed from an earlier shrine.